Obyektifikasi Konsep Perburuhan Islam di Indonesia - Jalil, Abdul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2006)
The problem of labor is one of the key issues in the global era that invokessome important questions concerning value, technicality of being human, and the notionof choice. The idea of labor is closely related to the realization of humanâs potentiality inits multidimensional complexity as well as with social structure and national identity ofman. This problem of labor is to do not only with economy, but also with social andpolitical system of a nation. In dealing with labor, there always been a tension betweencapital-owners, laborers, government and even international political power. As a religionthat is said to have made economics its âcurriculumâ, Islam does have an âobjectiviedâconcept of labor represented in a kind of partnership that combines shirkah âina>n andija>rah. This partnership necessitates that all parties involved share profit-loss, if any. Inthis way, no party âbe him laborer, capital-owner, or government- is loosing. Moreover,this system offers three advantages, e.g employee-ownership, production-sharing andprofit-sharing.